PairTilt: Design and Control of an Active Tilt‐Rotor Quadcopter for Improved Efficiency and Agility - Jerry Tang; Mark W. Mueller (Advanced Intelligent Systems, 2025)
This article presents PairTilt, a novel quadcopter design with two pairs of tiltable rotors, offering a balance between the simplicity of conventional quadcopters and the agility of complex tilt‐rotor systems. Despite being underactuated, with lateral motion not directly controlled, this design reduces complexity and energy consumption. The coupling of rotors reduces angular momentum issues, enhancing stability and efficiency without the challenges associated with tilting each motor individually, which would require higher servo torque due to significant gyroscopic torques. PairTilt's tiltable rotors enable agile maneuvers in confined spaces and reduce drag in high‐speed flight, extending operational range. The system's dynamics are analyzed, and a cascaded controller is implemented to ensure stable flight across various scenarios. Simulations and real‐world tests validate its superior agility, compact hovering, sensor pointing, and energy efficiency compared to conventional quadcopters. The primary contribution of this work lies in PairTilt's distinctive design, which achieves a unique balance of simplicity, efficiency, and agility. This balance is made possible by the pairwise rotor coupling, which reduces complexity and gyroscopic torque effects, and the prioritization of key degrees of freedom. This design approach opens new possibilities for aerial robotics applications requiring both maneuverability and efficient high‐speed flight.